Efektivitas Photoperiod Yang Berbeda Terhadap Kinerja Pertumbuhan Benih Lobster Air Tawar (Cherax Quadricarinatus) Yang Dipelihara Pada Alkalinitas 80 Mg/L. - mudzakirabdillanasution mudzakir; Teuku Fadlon Haser; Siti Komariyah (Universitas Mataram, 2024)
One of the freshwater commodities that is thought to have the potential to sell well on the world market in the future is freshwater lobster. This animal is a nocturnal animal commodity (animal that is active at night). This animal is thought to have the potential to sell well on the world market due to the high price and market demand which has not yet been met. Therefore, research efforts are needed on freshwater lobster seeds, to increase growth and survival. One of them is the use of alkalinity and photoperiod. The research design carried out was a Completely Randomized Design (CRD). consisting of 4 treatments with 3 repetitions. During the 40 day rearing period, pellets are given. Research shows that there are significant differences between each photoperiod in the growth of absolute weight, absolute length, molting percentage, daily growth rate and survival of freshwater crayfish. Treatments with different photoperiod times showed that the best results were obtained in treatment P2 with photoperiod time (16G:8T) and the lowest in treatment 3 (21G:3T). Based on research results, it is recommended that the use of photoperiod (16G:8T) is effective for increasing the growth and survival of freshwater lobsters. The results of this research can be used as information regarding the most effective photoperiod for freshwater lobsters